Effect Of Chinese Herb Danzhi Xiaoyao Pills On Pharmacokinetics Of Venlafaxine In Beagles - Zhu Y; Li S; Chen K; Ma K; Wu D; Qiu X (Drug Design, Development and Therapy, 2019)
Yong-liang Zhu, Shuang-long Li, Ke-li Chen, Kun-peng Ma, De-qian Wu, Xiang-jun Qiu Medical College of Henan University of Science and Technology, Luoyang 471023, People’s Republic of ChinaCorrespondence: Xiang-jun QiuMedical College of Henan University of Science and Technology, Luoyang 471023, People’s Republic of ChinaEmail lyxiangjun@126.comObjective: To investigate the effects of Chinese herb Danzhi Xiaoyao pills on the pharmacokinetics of venlafaxine and its metabolites O-desmethylvenlafaxine (ODV) and N-desmethylvenlafaxine (NDV) in beagles by using ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS).Methods: Six beagles (half male, half female) were chosen to test, being fasted before the experiment but having free access to drinking water 1 day before being fed drugs. After oral administration of venlafaxine hydrochloride tablets (10.28 mg/kg), the blood samples were collected in succession at different points in time. After 1-week washout period, Danzhi Xiaoyao pills (0.6g/kg) were given through oral administration to the six beagles every morning until the 7th day, venlafaxine hydrochloride tablets (10.28 mg/kg) were given after feeding Danzhi Xiaoyao pills (0.6g/kg) half an hour and blood samples were collected continuously at different points. All samples were analyzed by UPLC-MS/MS, and the main pharmacokinetic parameters of venlafaxine, ODV and NDV were computed by DAS 2.0.Results: The Cmax of the venlafaxine group (control group) and the combination group (experimental group) were (2267.26±252.89) ng/mL and (1542.64±190.73) ng/mL, respectively. The AUC(0-∞) of the two groups were (13,934.79±3609.23) ng·h/mL and (8001.91±2167.58) ng·h/mL, respectively. The ODV Cmax of the two groups were (2253.80±215.81) ng/mL and (2721.37±118.20) ng/mL, and AUC(0-∞) were (13,974.99±2784.04) ng·h/mL and (17,539.44±1894.29) ng·h/mL, respectively. The NDV Cmax of the two groups were (50.98±5.76) ng/mL and (58.74±12.33) ng/mL, and AUC(0-∞) were (179.26±34.94) ng·h/mL and (220.68±51.41) ng·h/mL, respectively. After administration of Danzhi Xiaoyao pills, the Cmax and AUC(0-∞) of venlafaxine decreased significantly, indicating that the plasma exposure of venlafaxine decreased. The increase of Cmax and AUC(0-∞) of ODV and NDV indicated a rise in plasma exposure.Conclusion: Danzhi Xiaoyao pills can accelerate the metabolism of venlafaxine in beagles. In clinical, when venlafaxine was co-administrated with Danzhi Xiaoyao pills, dose adjustment of venlafaxine should be taken into account.Keywords: beagle, UPLC-MS/MS, Danzhi Xiaoyao pills, venlafaxine, ODV, NDV, drug–drug interaction